Chinese international secondary school students as flexible citizens: toward cosmopolitan learning. Issue 4 (4th July 2022) - Wu, Xi; Tarc, Paul
ABSTRACT: Guided by the notion of 'flexible citizenship', as a strategy to accumulate and exchange different forms of capital across national borders, our ethnographic study followed eleven Chinese international secondary school students' transnational lives. This paper is focused on how instrumental goals of flexible citizenship cover over the emotional and existential qualities of these youths' lives. To orient this concern, we turn to Rizvi's conception of 'cosmopolitan learning' highlighting learners' relational awareness of their 'situatedness' in a hyper-connected world. Our analysis shows that student participants' understandings and practices were laced with emotional and moral sensitivities emerging from the intersecting transnational regimes of family, nation-states, and capital. Governed by home and host cultural logics and power discourses, the students were pushed and pulled into an instrumental flexible citizenship. They lacked dialogical spaces and pedagogical supports from teachers and parents for their cosmopolitan learning; we suggest stakeholders in East–West study abroad take notice.